Formação profissional para a atuação educacional com pessoas com transtorno do espectro do autismo - Bertazzo, Joíse de Brum (2015)
The Autistic Spectrum Disorder (ASD) is a behavioral syndrome whose indicative signs are already perceived in the early years of childhood. Considering the development as sensitive in particular to the early experiences of the child in the environment, early diagnosis and educational interventions are indicated consensus in the literature as catalysts of development in cases of ASD. There fore vocational training geared to the specific disorder that enables those responsible for this intervention is needed. From this, we elaborated this work in order to develop a program for training professionals in the fields of health and education for educational activities with people with ASD and evaluate its effectiveness. For that were identified through the literature review, which the knowledge necessary for teachers to work with students with ASD and from the systematization of this knowledge, built a curriculum for a training course aimed at professionals working in favor education of people with ASD. From the curriculum the study was conducted with a sample of eight professionals in the fields of health and education of a gaucho municipality. This was a survey applied quantitative and qualitative nature which offered and assessed the effectiveness of a training course for 30h with psychopedagogy, special educators, speech therapists and psychologists members of the Center for Specialized care in the city of Santiago/Rio Grande do Sul. The training included knowledge necessary for the care of people with ASD, including explanatory theories, characterization, evaluation of the syndrome, and intervention possibilities. The effectiveness of the course is evaluated both by module, as this as a whole, as well as maintaining knowledge and social validity formation was evaluated. The data coming from the realization of this study were submitted to content analysis and descriptive statistics. The main results was that the course was effective and that there have been important advances in knowledge and perception of participants regarding the person with ASD and, moreover, had a consistent impact in reality it was intended, considered as positive the validity social.